2018
DOI: 10.1111/hsc.12538
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting general practice collaboration with voluntary and community sector organisations

Abstract: Collaborative working between general practice (GP) and voluntary and community sector (VCS) organisations is increasingly championed as a means of primary care doing more with less and of addressing patients' "wicked problems". This paper aims to add to the knowledge base around collaborative practice between GPs and VCS organisations by examining the factors that aid or inhibit such collaboration. A case study design was used to examine the lived-experience of GPs and VCS organisations working collaborativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 27 publications
3
58
0
Order By: Relevance
“…Persuading patients that social interventions are an acceptable alternative to a medical prescription is a complex issue, but HCPs must reframe patient beliefs about suitability as this is known to contribute to successful uptake [ 33 ]. Furthermore, a cohesive and integrated healthcare approach to social prescribing is necessary to achieve community wide impact, yet this study and others have identified a need to improve communication and trust between medical prescribers and social prescribers and deliverers [ 15 , 34 ]. PARS demonstrate that patients are willing to accept “social prescriptions”, being a well-established pathway for HCPs to encourage patient PA [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Persuading patients that social interventions are an acceptable alternative to a medical prescription is a complex issue, but HCPs must reframe patient beliefs about suitability as this is known to contribute to successful uptake [ 33 ]. Furthermore, a cohesive and integrated healthcare approach to social prescribing is necessary to achieve community wide impact, yet this study and others have identified a need to improve communication and trust between medical prescribers and social prescribers and deliverers [ 15 , 34 ]. PARS demonstrate that patients are willing to accept “social prescriptions”, being a well-established pathway for HCPs to encourage patient PA [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…It also appears to rely on GP "buy-in" to validate the service among other professionals and patients, and requires GPs to believe in the link worker's ability and in the benefits of social prescribing [22]. Further, a few studies have included interviews with GPs, but these have tended to involve a very small number of GP interviews, or focused solely on 1 practice or locale [24,25]. Nevertheless, this preliminary research does demonstrate that GPs found it challenging to have good knowledge of community groups or the time to engage fully, but valued face-to-face meetings with them [24].…”
Section: Introductionmentioning
confidence: 99%
“…Further, a few studies have included interviews with GPs, but these have tended to involve a very small number of GP interviews, or focused solely on 1 practice or locale [24,25]. Nevertheless, this preliminary research does demonstrate that GPs found it challenging to have good knowledge of community groups or the time to engage fully, but valued face-to-face meetings with them [24]. GPs were also reported to find it difficult to address patient's social and mental health needs, due to lack of training and limited time in appointments; GPs acknowledged the limitations of the "traditional medical model" [25].…”
Section: Introductionmentioning
confidence: 99%
“…An evaluation of a discrete social prescribing scheme mentioned the importance of a shared vision and language across primary care and the CVSOs they are working with, relationship and partnership building, and the importance of a CVS infrastructure to support this [27]. Similarly, case studies of partnerships between GPs and the CVS have identified clashes of culture and 'negative perceptions' internally, in addition to external challenges including lack of funding, unclear referral pathways, and high staff turnover [28,29]. Factors that were mentioned as important for strengthening the relationships between the providers were 'mutual respect' and equality within the relationship,and 'early stakeholder engagement' [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, case studies of partnerships between GPs and the CVS have identified clashes of culture and ‘negative perceptions’ internally, in addition to external challenges including lack of funding, unclear referral pathways, and high staff turnover [ 28 , 29 ]. Factors that were mentioned as important for strengthening the relationships between the providers were ‘mutual respect’ and equality within the relationship,and ‘early stakeholder engagement’ [ 28 , 29 ]. However, there are still major gaps in understanding these barriers, including around identifying the barriers faced by organisations in undertaking work with individuals with mental illness outside of formal social prescribing schemes.…”
Section: Introductionmentioning
confidence: 99%